ANALISIS KONSEP DAN IMPLEMENTASI TAFSIR TARBAWI SEBAGAI LANDASAN PENDIDIKAN QUR’ANI - Arif Atma Mahendra; Darul Mustofa; Ainal Gani; Muhammad Akmansyah; Amirudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the concept and scope of tafsir tarbawi as a Qur’anic interpretive approach that emphasizes educational values, character formation, and the development of human potential based on divine guidance. The problem addressed in this article is the lack of comprehensive understanding regarding how educational principles in the Qur’an can be systematically extracted through tafsir tarbawi and applied to contemporary Islamic education. The purpose of this study is to identify the essential concepts of tafsir tarbawi, outline its theoretical foundations, and explain its relevance to current educational challenges. This research employs a qualitative library research method, analyzing classical and contemporary tafsir works as well as literature on Islamic education. The analysis reveals that tafsir tarbawi focuses on extracting pedagogical values from Qur’anic verses, including principles of faith education, moral cultivation, character development, balance between worldly and spiritual aspects, and dialogical methods in teaching. Furthermore, the study highlights key educational principles embedded in the Qur’an, such as tauhid as the foundation of education, exemplary behavior as a method of value internalization, wisdom and dialogue as pedagogical approaches, and holistic human development as the ultimate goal. The findings indicate that tafsir tarbawi provides a strong epistemological basis for constructing a comprehensive Islamic education framework that integrates cognitive, affective, and behavioral dimensions. Therefore, tafsir tarbawi is highly relevant for responding to modern educational challenges, strengthening Islamic identity, and shaping a generation with strong character, spiritual depth, and intellectual competence. Overall, this study affirms the importance of tafsir tarbawi as a strategic approach in grounding educational practices in Qur’anic principles.